Uji Aktivitas Ekstrak Daun Seledri ( Apium graveolens L.) terhadap Kumbang Kacang Callosobruchus chinensis L. (Coleoptera:Bruchidae) - NI NENGAH DARMIATI (Fakultas Pertanian Universitas Udayana, 2013)
The Activity Test of Celery Leaf Extract (Apium graveolens L.) Against Bean Weevil, Callosobruchus cinensis L. (Coleoptera:Bruchidae) The experiment was conducted at the Laboratory of Plant Pest and Disease Management,Department of Agroecotechnology, Faculty of Agriculture, Udayana University. The purpose of this experiment was to examine the activity of celery leaf extract against bean weevil, Callosobruchus chinensis L. The experiment was Randomized Complete Design, with five treatments of formulation concentration. The activities of celery leaf extract was indicated through i.e. contact poison test, repellent test, and the placement of eggs (oviposition) test. The results showed that the celery leaf extract has activity as a contact poison with concentration 75% formulations caused over 50% death of the total insect. The extract with 100% concentration acted as a repellent and anti oviposition as well.